Sarah Kofman: Effecting Self Translation - McDonald, Christie (TTR)

(untitled) (Association canadienne de traductologie, 1998)
AbstractSarah Kofman : Effecting Self Translation — In Sarah Kofman's work, philosophical and psychoanalytical analysis modulate into "life writing" and create a kind of translation which neither alone can fully explain. For Kofman, translation in this sense goes back to readings in philosophy, psychoanalysis and linguistics in order to effect change. Reading Nietzsche through Freud, and Freud through Nietzsche, Sarah Kofman unleashes powerful analytical tools from which emerge a very personal kind of writing in Rue Ordener, rue Labat. What is at stake is the destiny of woman, the extraordinary story of this woman-writer-philosopher and the relationship between life and thought.